STUDY OF ALGICLAM INFLUENCE ON CERTAIN HEALTH INDICATORS AT RADIATION INJURY - T. V. Ponomareva; N. M. Vishnyakova (Радиационная гигиена)
The article presents the study of Algiclam influence on the body mass, longevity and incidence of malignant neoplasms for scrub white rats of various gender, exposed in the sublethal doze in the chronic experiment. The study revealed that Algiclam has obvious radioprotecting action on these integral indicators of viability and physical conditions of homoiothermal animals. Obtained experimental results indicates the possibility of Algiclam dietary supplement application for the reduction or prevention of negative radiation injury manifestations.